Step-by-step explanation:
First, replace f(x) with y . ...
Replace every x with a y and replace every y with an x .
Solve the equation from Step 2 for y . ...
Replace y with f−1(x) f − 1 ( x ) . ...
Verify your work by checking that (f∘f−1)(x)=x ( f ∘ f − 1 ) ( x ) = x and (f−1∘f)(x)=x ( f − 1 ∘ f ) ( x ) = x are both true.
Answer:
You stopped at 2y-4=12
If we add same number to both sides the equation will remain true. For example if we have 5=5, and we add 7 to both sides, we get 12=12 which is also true. Now let's do this with our equation. Add 4 to both sides(to have only y on the left side). We get 2y=16, hence y=8.
Answer. 2y=16
Answer:
![ab-2bc+ca](https://tex.z-dn.net/?f=ab-2bc%2Bca)
Step-by-step explanation:
Complete question is given below
Add:-
ab-bc+ac,bc-ca+ab,ca-ab-2bc
We have to find the result after addition
Now, adding all expression
We get
![ab-bc+ac+bc-ca+ab+ca-ab-2bc](https://tex.z-dn.net/?f=ab-bc%2Bac%2Bbc-ca%2Bab%2Bca-ab-2bc)
Combine like terms then, we get
![(ab+ab-ab)+(bc-bc-2bc)+(ac-ca+ca)](https://tex.z-dn.net/?f=%28ab%2Bab-ab%29%2B%28bc-bc-2bc%29%2B%28ac-ca%2Bca%29)
![ab-2bc+ca](https://tex.z-dn.net/?f=ab-2bc%2Bca)
Hence,![ab-bc+ac+bc-ca+ab+ca-ab-2bc=ab-2bc+ca](https://tex.z-dn.net/?f=ab-bc%2Bac%2Bbc-ca%2Bab%2Bca-ab-2bc%3Dab-2bc%2Bca)
Let's say, the amount that each side was increased was "a"
so, it was 5 wide and 12 long, now it's 5+a wide and 12+a long
we know the area is 120, so whatever "a" is, we know that
(5+a)(12+a) = 120
so
![\bf (5+a)(12+a) = 120\implies 60+17a+a^2=120 \\\\\\ a^2+\underline{17} a\underline{-60}=0\qquad \qquad \begin{cases} 20\cdot -3\implies \underline{-60}\\\\ 20-3\implies \underline{17} \end{cases}](https://tex.z-dn.net/?f=%5Cbf%20%285%2Ba%29%2812%2Ba%29%20%3D%20120%5Cimplies%2060%2B17a%2Ba%5E2%3D120%0A%5C%5C%5C%5C%5C%5C%0Aa%5E2%2B%5Cunderline%7B17%7D%20a%5Cunderline%7B-60%7D%3D0%5Cqquad%20%5Cqquad%20%0A%5Cbegin%7Bcases%7D%0A20%5Ccdot%20-3%5Cimplies%20%5Cunderline%7B-60%7D%5C%5C%5C%5C%0A20-3%5Cimplies%20%5Cunderline%7B17%7D%0A%5Cend%7Bcases%7D)
use those factors, solve for "a"
Answer:
128.69.
Step-by-step explanation:
The variance is np(1 - p)
= 625*(0.28) * 0.71
= 128.69.